Mobile Technology Use and Its Association With Executive Functioning in Healthy Young Adults: A Systematic Review - Warsaw, Rachel E.; Jones, Andrew; Rose, Abigail K.; Newton-Fenner, Alice; Alshukri, Sophie; Gage, Suzanne H. (Frontiers in Psychology, 2021)
Introduction: Screen-based and mobile technology has saturated society at an unprecedented rate. However, little is understood about whether screen use affects executive functioning (EF), the range of mental processes that aid goal attainment and facilitate the selection of appropriate behaviours. To examine this, a systematic review was conducted. Method: A comprehensive literature search was conducted using Web of Science, MEDLINE, PsycINFO and Scopus databases to identify articles published between 2007 and March 2020, examining the use of mobile technologies on aspects of EF in healthy adults aged 18-35 years. In total 6079 articles were screened by title, and 39 screened by full text. Eight eligible papers were identified for inclusion. Our methods were pre-registered on the PROSPERO international prospective register of systematic reviews. Results: A total of 768 438 participants were included across the eight studies. Four Five of the eight studies examined more than one EF. and four Five studies measured inhibition, and four studies measured decision-making respectively. Smartphone use was negatively associated with inhibition and decision-making. Working memory performance was found to be improved by increased time engaging in video games and by refraining from smartphone use prior to bedtime. Quality assessments indicated the studies were at risk of methodological bias and had low quality of evidence for determining the relationship between technology use and executive functioning. Conclusions: This review highlights the scarcity of the literature in this area. It presents a call-to-action for rigorous and objective research to further our understanding of the impact of mobile technology on different aspects of executive function.